Drug interactions between antiretrovirals and drugs used to treat benign prostatic hyperplasia/lower urinary tract symptoms. (2nd October 2016) - Kreutzwiser, Denise; Tseng, Alice
ABSTRACT: Introduction : Significant advances in antiretroviral (ARV) therapy have transformed HIV into a chronic manageable disease. Co-morbidities associated with aging, such as benign prostatic hyperplasia (BPH), are becoming increasingly prevalent in the HIV-infected population. The pharmacological treatment of BPH involves medications mainly metabolized by CYP 450 enzymes, while many ARVs have inducing or inhibiting effects on the CYP 450 system. Consequently, there is potential for significant pharmacokinetic (PK) interactions between these two classes of medications. Areas covered : This article reviews the pharmacology and metabolism of selected BPH drug therapies and ARVs, in addition to highlighting potential interactions between these two drug categories. The authors also present PK evidence of interactions from available clinical trials, product monographs and international conference abstracts. Potentially significant drug interactions are summarized and strategies for management are discussed. Expert opinion : Drugs most likely to interact with BPH medications include protease inhibitors, the non-nucleoside reverse transcriptase inhibitors efavirenz, nevirapine, etravirine, and the cobicistat-boosted integrase inhibitor elvitegravir. Clinically significant PK interactions with BPH medications and dolutegravir, raltegravir, rilpivirine, or the investigational agent doravirine do not appear to exist. Clinicians working with HIV-infected individuals need to recognize the potential for interactions involving BPH and ARV treatments to ensure effective and safe drug therapy use.